1996
DOI: 10.1029/95jb03732
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelastic properties of MgSiO3 perovskite determined by in situ X ray observations up to 30 GPa and 2000 K

Abstract: In situ X ray experiments on MgSiO 3 perovskite at pressures of 21 -29 GPa and temperatures of 300-2000 K were carried out using an MA8-type high-pressure apparatus, employing sintered diamond anvils, combined with synchrotron radiation. The thermal expansion at 25 GPa up to 2000 K was determined from interpolation of the P-V-T data obtained in the present study. The 95% confidence level was estimated by taking all possible errors into account, including statistical error and systematic error caused by uncerta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
112
2
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(130 citation statements)
references
References 34 publications
15
112
2
1
Order By: Relevance
“…[12] The lattice volume of MgSiO 3 Pv has been measured by a number of authors, and the reported values of the lattice volume range from 162.0 to 162.75 Å 3 [Liu, 1974;Ito and Matsui, 1978;Yagi et al, 1978;Mao et al, 1991;Wang et al, 1994;Funamori et al, 1996;Fiquet et al, 1998]. In this study, the lattice parameters of MgSiO 3 Pv were determined precisely using 33 diffraction peaks and the lattice volume was found to be 162.373 (16) Table 3.…”
Section: X-v Relationship In (Mgfe)sio 3 Perovskitementioning
confidence: 99%
“…[12] The lattice volume of MgSiO 3 Pv has been measured by a number of authors, and the reported values of the lattice volume range from 162.0 to 162.75 Å 3 [Liu, 1974;Ito and Matsui, 1978;Yagi et al, 1978;Mao et al, 1991;Wang et al, 1994;Funamori et al, 1996;Fiquet et al, 1998]. In this study, the lattice parameters of MgSiO 3 Pv were determined precisely using 33 diffraction peaks and the lattice volume was found to be 162.373 (16) Table 3.…”
Section: X-v Relationship In (Mgfe)sio 3 Perovskitementioning
confidence: 99%
“…[2] The perovskite (pv) structure of (Mg, Fe)SiO 3 is considered to be the most abundant phase in the lower mantle, which makes its high-pressure, high-temperature behavior a matter of some interest. Of particular importance, given seismic ultra-low velocity zones (ULVZs) [Williams and Garnero, 1996] above the core-mantle boundary, are constraints on the phase relations and density contrasts among mantle solids, mantle melts, and the core that may explain the presence and stability of partial melting at the very base of the mantle [Montague and Kellogg, 2000;Namiki, 2003;Zhong and Hager, 2003].[3] The thermal EOS of MgSiO 3 pv has been constrained by numerous static experiments and computational studies [Wang et al, 1994;Utsumi et al, 1995;Funamori et al, 1996;Saxena et al, 1999;Fiquet et al, 2000;Karki et al, 2001;Marton et al, 2001;Brodholt et al, 2002]. Previous dynamic pressure-density-internal energy (P-r-E) data for MgSiO 3 composition are compiled in Marsh [1980] and Simakov and Trunin [1973].…”
mentioning
confidence: 99%
“…The isothermal bulk modulus of MgSiO 3 and (Mg,Fe)SiO 3 perovskites have been established to generally fall within the range 250 260 GPa by numerous laboratories (e.g., Funamori et al, 1996;Fiquet et al, 1998;Fiquet et al, 2000;Sinogeikin et al, 2004); however measurements on perovskite compositions incorporating Al (hence stabilising some of the iron, if present, as Fe 3+ ) show dramatically different results, but with a large variation in observed behaviour. Some high pressure measurements show a 5 10% decrease in bulk modulus (Zhang and Weidner, 1999;Kubo et al, 2000;Daniel et al, 2001;Yagi et al, 2004), some show an increase in bulk modulus Ono et al, 2004) and some show no change (Yagi et al, 2004;Jackson et al, 2004).…”
Section: +mentioning
confidence: 99%